DEVELOPMENT OF A POINT OF CARE DIAGNOSTIC PLATFORM FOR DENGUE VIRUS DETECTION - Savitri, Dita Nurul; Kiri, Ming; Dara, Ravi (Yayasan Adra Karima Hubbi, 2025)
Dengue fever is a significant health threat in tropical and subtropical regions, with current diagnostic methods requiring well-equipped laboratories and skilled personnel. Early detection is crucial for effective management and control. To develop a reliable, rapid, and user-friendly point-of-care diagnostic platform for dengue virus detection, suitable for use in low-resource settings. The study utilized a multi-disciplinary approach, integrating microfluidics, biosensors, and nanotechnology. Blood samples from suspected dengue patients were analyzed using the newly developed platform. Comparative analysis was conducted against conventional diagnostic methods. The new point-of-care platform demonstrated a sensitivity of 90% and specificity of 85%, providing results in an average of 15 minutes. This performance marks a significant improvement over conventional methods, which are slower and less accurate. The integration of advanced technologies into a point-of-care diagnostic platform has significantly enhanced the accuracy and speed of dengue virus detection. Further clinical trials are necessary to validate these findings and ensure the platform's efficacy and scalability in real-world settings.